Can Fiber Application Affect the Fracture Strength of Endodontically Treated Teeth Restored with a Low Viscosity Bulk-Fill Composite?. (22nd January 2019) - Eliguzeloglu Dalkılıç, Evrim; Kazak, Magrur; Hisarbeyli, Duygu; Fildisi, Mehmet Ali; Donmez, Nazmiye; Deniz Arısu, Hacer
Abstract : Objective. The aim of this study is to evaluate the effects of different fiber insertion techniques and thermomechanical aging on the fracture resistance of endodontically treated mandibular premolar teeth restored using bulk-fill composites. Materials and Methods . Eighty human mandibular premolar teeth were randomly divided into eight groups: Group IN, Group BF, Group PRF1, Group PRF2, Group IN-TMA, Group BF-TMA, Group PRF1-TMA, and Group PRF2-TMA. Group IN (intact) and Group IN-TMA (intact but subjected to thermomechanical aging) served as control groups. In the other six groups, endodontic treatment was performed and standardized mesio-occluso-distal (MOD) cavities were prepared. In BF, PRF1, and PRF2, the cavities were restored with bulk-fill composite only, bulk-fill/Ribbond, and bulk-fill/additional Ribbond, respectively. In BF-TMA, PRF1-TMA, and PRF2-TMA, the teeth were subjected to thermomechanical aging after the restorations. All of the teeth were fractured on the universal testing machine. Fracture surfaces were analyzed with a stereomicroscope. Results. Control groups showed significantly higher fracture strengths than tested groups ( P <0.05). No statistically significant difference was observed among the tested groups ( P >0.05). Most of the favorable fractures were seen in PRF1, PRF2, and PRF2-TMA. Most of the unfavorable fractures were seen in BF-TMA. Conclusions . Although fiber insertion with different techniques did not increase the fracture strength of teeth restored with bulk-fill composites, it increased the favorable fracture modes. Thermomechanical aging did not change the fracture strength of the groups.